2022
DOI: 10.1155/2022/7207755
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Cycles of Binge-Like Ethanol Exposure Induces Neurobehavioral Changes During Short- and Long-Term Withdrawal in Adolescent Female Rats

Abstract: Alcohol consumption is spread worldwide and can lead to an abuse profile associated with severe health problems. Adolescents are more susceptible to addiction and usually consume ethanol in a binge drinking pattern. This form of consumption can lead to cognitive and emotional disorders, however scarce studies have focused on long-term hazardous effects following withdrawal periods after binge drinking in adolescents. Thus, the present study aims at investigating whether behavioral and cognitive changes persist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…If anything, relative to controls, CSR rats showed a tendency towards a less anxious-like behavior in the open field test and in the NSF test. At first glance, these results could appear counterintuitive because existent reports showed that repeated adolescent alcohol binge drinking [75] and sleep loss [76] can increase anxiety and depressive symptoms in early and mid- adulthood. On the other hand, it is also known that disrupted sleep is associated with global risky decision making in adolescents, including illicit substance use, sexual risk-taking, and road/transport-related safety [10].…”
Section: Discussionmentioning
confidence: 99%
“…If anything, relative to controls, CSR rats showed a tendency towards a less anxious-like behavior in the open field test and in the NSF test. At first glance, these results could appear counterintuitive because existent reports showed that repeated adolescent alcohol binge drinking [75] and sleep loss [76] can increase anxiety and depressive symptoms in early and mid- adulthood. On the other hand, it is also known that disrupted sleep is associated with global risky decision making in adolescents, including illicit substance use, sexual risk-taking, and road/transport-related safety [10].…”
Section: Discussionmentioning
confidence: 99%
“…The animals were weekly weighted to adjust the dose. The binge-like EtOH administrations aimed to simulate a pattern of compulsive consumption for 4 weeks [22,24,43].…”
Section: Drinking Protocolmentioning
confidence: 99%